Bone degradation at five Arctic archaeological sites: Quantifying the importance of burial environment and bone characteristics. (January 2021) - Matthiesen, Henning; Høier Eriksen, Anne Marie; Hollesen, Jørgen; Collins, Matthew
Abstract: The degradation of archaeological bones is influenced by many variables. The bone material itself is a composite of both organic and inorganic components, and their degradation depends on processes occurring both before and after burial, and on both intrinsic bone characteristics as well as extrinsic environmental parameters. In this study we attempt to quantify the effect of some of the variables using a novel approach that includes detailed monitoring of the burial environment combined with respirometry studies of bone material from five archaeological sites in West Greenland. First, we compare the state of preservation of excavated bone material with the current burial environment including the soil pH, thawing degree days, soil porosity and soil moisture. Secondly, we investigate oxic degradation of collected bone samples through respirometry and quantify the effects of temperature and moisture on the oxidation rate of individual bones. Finally, we discuss how the oxidation rate is influenced by intrinsic bone parameters. Some of the main conclusions are: 1) There is a significant correlation between the current burial environment and the current state of preservation of the bones. 2) The oxidation rate measured by respirometry increases on average fourfold as temperature increases by 10 °C, and more than hundred-fold when dry bones are soaked in water. 3) The oxidation rate of different bones varies over two orders of magnitude due to intrinsic variables such as organic content and state of preservation of the bones. 4) The median oxidation rate of wet bone at 15 °C corresponds to a yearly loss of 3.8% of their mean organic content, while the median yearly loss for dry bones at 75% RH is 0.02%. 5) Respirometry is a promising tool for quantitative degradation studies of bone, but more studies are needed in order to obtain a better understanding of the oxidation processes involved. Highlights: Respirometry and environmental monitoring allow quantitative degradation studies of bone. State of preservation of bones correlate closely to burial environment at five Arctic sites. Bone oxidation rate increases fourfold as temperature increases by 10 °C and more than hundred-fold when dry bones are soaked. The oxidation rate of different bones varies depending on organic content and preservation state. Oxidation rates measured in the laboratory are realistic when compared to field observations.